Development of Fistula in a Patient With Crohn's Disease: a case report - GÜL, ASİYE (My University, 2019)
INTRODUCTION: A fistula is an abnormal connection between two epithelized surfaces. 15- 25% of the fistulas develop spontaneously and 75-85% develop after surgery. Spontaneous fistulas develop after radiotherapy, diverticulitis, appendicitis, peptic ulcer perforation, pancreatitis, intestinal tuberculosis, inflammatory bowel disease. Malnutrition, sepsis, shock, circulatory failure, corticosteroid treatment, difficulties in surgical anastomosis cause fistula formation. Fistula develops 20% -40% with Crohn's disease. 75% of intestinal fistulas open to the skin. It has psychological, physiological, sociological and economic effects in patients with fistula. Objective: In this study, it was emphasized the importance of nursing care of a patient with Crohn's disease, difficult management, and long-standing fistula. Case: Mr. ET who has Crohn's disease, is 27 years old, married, graduated from primary school, lived in the village outside of Istanbul. The patient admitted to the emergency department with severe abdominal pain at the time of his visit to his brother. The emergency operation performed due to Ileus and common small intestinal dilatation. Segmenter small intestine resection and ileostomy performed and the patient followed up in the intensive care unit. Because of intraabdominal abscess, a vacuum system is applied. Afterward, two fistulas developed in the abdominal region. The total parenteral and enteral food is used for weight loss. Antibiotic therapy initiated for infection. Three months later, the fistula healed and the patient discharged on his own request. Conclusion: Complicated nursing care and multidisciplinary care must be provide for the problems that may occur in the patient who is hospitalize for a long time after the fistula.
Keywords: Nursing; Fistula; Care; Hemşirelik; Fistül; Bakım